In vitro Acetylcholinesterase Inhibitory Activity of Different Capsicum Varieties by using Chicken Brain Extract Prepared by Employing a Home Mixer-jar as an Alternative to Expensive Tissue Homogenizer - Pandy, Vijayapandi; Shaik, Baji Rahamtulla; Chunduru, Divyasri; Munnangi, Dharani (Indian Journal of Pharmaceutical Education and Research, 2022)
Objectives: The present study aimed to investigate acetylcholinesterase (AchE) inhibitory activity of methanolic extract of different capsicum varieties using isolated chicken’s brain homogenate as an alternative for rodent’s brain homogenate by Ellman’s in vitro assay. In this study, we used a home mixer-jar as a substitute for the expensive tissue homogenizer to mince the chicken brain along with conventional hand motorpestle homogenization technique. Materials and Methods: This in vitro AchE inhibition assay was performed as described by Ellman et al. (1961) with minor modifications. Results: The IC50 values in ng/ml of the reference drug, neostigmine were found to be 149.92±37.72 and 347.22±81.50 using mortar and pestle (MP), and mixer-jar (MJ) method of tissue homogenization techniques, respectively. The IC50 values in μg/ml of the methanolic extract of different varieties of capsicum were found to be: red chilli by MP method 1786.1±118.52; by MJ method 1858.5 ±136.79, green chilli by MP method 1418.8±94.16; by MJ method 1786.1±118.52and green capsicum (bell pepper) by MP method 2022.8±244.5; by MJ method1813.3 ±45.63, respectively. Furthermore, it was noted that the yield of AchE in brain extract prepared using a mixer jar was high when compared with the brain homogenate prepared using the mortar and pestle. Conclusion: The use of chicken brain and employing mixer-jar for brain homogenization are evolved as good alternatives for unnecessary killing of laboratory animals and for the brain tissue homogenization. All capsicum varieties (green chilli, red chilli, and green capsicum) showed AchE inhibitory effect in in vitro Ellman’s assay.
Keywords: Chicken brain; Mortar and pestle; Mixer jar; Neostigmine; Capsicum extracts; Acetylcholinesterase; Ellman’s assay